Advance directives among community-dwelling stroke survivors - Gupta, Soumya; Chen, Bridget J.; Suolang, Deji; Cooper, Rachel; Faigle, Roland (PloS one, 2023)
Advance directives (ADs) are integral to health care, allowing patients to specify surrogate decision-makers and treatment preferences in case of loss of capacity. The present study sought to identify determinants of ADs among stroke survivors. In this cross-sectional study (Care Attitudes and Preferences in Stroke Survivors [CAPriSS]), community-dwelling stroke survivors were surveyed on ADs; validated scales were used to query palliative care knowledge and attitudes towards life-sustaining treatments. Logistic regression was used to determine variables associated with ADs. Among 562 community-dwelling stroke survivors who entered the survey after screening questions confirmed eligibility, 421 (74.9%) completed survey components with relevant variables of interest. The median age was 69 years (IQR 58-75 years); 53.7% were male; and 15.0% were Black. Two hundred and fifty-one (59.6%) respondents had ADs. Compared to stroke survivors without ADs, those with ADs were more likely to be older (median age 72 vs. 61 years; p<0.001), White (91.2% vs. 75.9%, p<0.001), and male (58.6% vs. 46.5%, p = 0.015), and reported higher education (p<0.001) and income (p = 0.011). Ninety-eight (23.3%) participants had "never heard of palliative care". Compared to participants without ADs, participants with ADs had higher Palliative Care Knowledge Scale (PaCKS) scores (median 10 [IQR 5-12] vs. 7 [IQR 0-11], p<0.001), and lower scores on the Attitudes Towards Life-Sustaining Treatments Scale (indicating a more negative attitude towards life-sustaining treatments; median 23 [IQR 18-28] vs. 29 [IQR 24-35], p<0.001). Multivariable logistic regression identified age (OR 1.62 per 10 year increase, 95% CI 1.30-2.02; p<0.001), prior advance care planning discussion with a physician (OR 1.73, 95% CI 1.04-2.86; p = 0.034), PaCKS scores (OR 1.06 per 1 point increase, 95% CI 1.01-1.12; p = 0.018), and Attitudes Towards Life-Sustaining Treatments Scale scores (OR 0.91 per 1 point increase, 95% CI 0.88-0.95; p<0.001) as variables independently associated with ADs. Age, prior advance care planning discussion with a physician, palliative care knowledge, and attitudes towards life-sustaining treatments were independently associated with ADs.